الأثر المضلل للتطبيق المنفرد للمعيار المحاسبي الدولي رقم (21) على مستخدمي القوائم المالية في المصارف السورية الخاصة - القاضي, حسين; هاشم, محمد (Latakia University Journal - Economic and Legal Sciences Series, 2016)
تهدف هذه الدراسة إلى التعرف على تأثير تطبيق المعيار المحاسبي الدولي رقم 21 ( آثار التغيرات في أسعار العملات الأجنبية ) وأخذه بعين الاعتبار عند إعداد نتائج أعمال المصارف الخاصة السورية، وتركيزها عليه مع إغفال التغيرات التي طرأت على قيمة البنود والعناصر الأخرى في المركز المالي نتيجة تغيرات المستوى العام لأسعار العملة المحلية، مما من شأنه أن يعطي نتائج مضللة وغير سليمة لمستخدمي تلك البيانات والمعلومات المالية المعتمدة عليها في اتخاذ قراراتها الاستثمارية كل من وجهة نظره , ومعرفة التغيرات التي ستطرأ على النتائج والمخرجات بعد استبعاد تلك الأرباح التي نجمت عن التغيرات في أسعار العملات الأجنبية . عمدت الدراسة إلى تسليط الضوء على الأثر الكبير الذي ظهر على النتائج الختامية من ربح أو (خسارة )، من شأنه أن يؤثر على صحة وسلامة المخرجات ،لا سيما أنها أسهمت بشكل فعال في إطفاء ( الخسائر ) الناجمة فعلاً من النشاطات التقليدية و الخدمات الفعلية المقدمة من قبل تلك المصارف , بالإضافة إلى التغير في مدلولات النسب المالية والتحليلية المعتمدة من قبل مستخدمي تلك البيانات والمعلومات . وخلصت الدراسة إلى التوصيات بناء على النتائج السابقة , ومن أهمها ضرورة أخذ التغيرات التي طرأت في المستوى العام للأسعار بعين الاعتبار على مختلف عناصر وبنود قوائم وبيانات النتائج المالية بالسوية نفسها التي أخذت بها التغيرات في أسعار العملات الأجنبية , وضرورة مراعاة مراجعي الحسابات لسلامة الإفصاح في قوائم المصارف المالية المنشورة ،وأن يبدوا رأيهم بكل شفافية وموضوعية , ومحاولة إقناع إدارات المصارف بضعف دلالة تلك التقارير والبيانات وضرورة تعديلها لتكون أكثر شفافية. The study aims to show the effect of implementing the above mentioned accounting standard No 21 and the effect of hard currency prices , taking it into concideration when preparing the results of the private Syrian banks activities . We should concentrate on it disregarding the changes that happened to the value of terms and other elements in the financial statments due to the general level of changes of the prices of the local currency . this will give misleading and incorrect results to data users and the financial information depended upon in taking its investment decisions , each from his own point of view . The study realises the changes that will affect the financial results after excluding the profits which result from the changes in the prices of foreign currency . The study has shed light on the great impact on the final results of profit or loss , after excluding the effect of accounting standard No 21 , which will affect the accuracy of the outcome , especially if it seriously leads to hiding the losses resulting from traditional activities and the actual services provided from these banks , in addition to the change of the applied analytical and financial rate on the part of the users of these data and information Also , the study has given a number of recommendations taking into account the previous results. the most important is the necessity of taking the general price changes into consideration , regarding all different elements of terms , lists and financial outcome , the same as the changes that happened to the prices of the foreign currency . it is essential that officials who check the accounts must clearly reveal the financial lists of the banks objectively and transparenly .we should try to convince banks mangements how weak the evidence of these reports and lists are, because they don’t express reality with transparecy .